Pengaruh Pertumbuhan Ekonomi Sektor Primer, Sekunder dan Tersier terhadap Kemiskinan di Provinsi Kalimantan Barat - B1011151003, LAILA (Jurnal Pembangunan dan Pemerataan, 2019)
AbstrakEconomic growth is an important indicator that can explain how the role of each sector, namely the primary, secondary and tertiary sectors in overcoming poverty that occurs in the Province of West Kalimantan. The purpose of this study was to analyze the effect of economic growth in the primary, secondary and tertiary sectors on poverty in the province of West Kalimantan. The method used in this study is quantitative with a descriptive statistical approach. The results of the study show that partially the economic growth of the primary and secondary sectors has a negative and significant effect, but the growth of the tertiary sector has a positive and significant effect on the poverty of the Province of West Kalimantan. The variables in the model together have an influence of around 97.12 percent on poverty, while 2.88 percent is influenced by other variables. Keywords: Poverty, Primary Sector Economic Growth, Secondary Sector Economic Growth and Tertiary Sector Economic Growth ReferensiAmir, A. (2007). Pembangunan dan Kualitas Pertumbuhan Ekonomi Dalam Era Globalisasi. Bogor: Biografika.Arsyad, L. (2006). Pengantar Perencanaan dan Pembangunan Ekonomi Daerah, Edisi Pertama ,Yogyakarta: BPFEArsyad, L. (2015). Ekonomi Pembangunan. Edisi ke lima. Yogyakarta: UPP STIM YKPN.Jayadi, S. D. (2016). Peran Pertumbuhan Ekonomi dalam Menurunkan Kemiskinan di Tingkat Provinsi di Indonesia Tahun 2004–2012. Modus, 28 (1): 87-99.Kuncoro, M. (2010). Dasar- Dasar Ekonomika Pembangunan. Yogyakarta: UPP STIM YKPN.Sharp, A. M. (1996). Charles A.R., & Paul, W.C. Economics of social issues, edisi ke 12, Richard D. I, Chicago bab VII.Sobia Rose, S., Abbas, S., Ali, F.M., & Azeem, M. M. (2013).  Growth-Poverty Linkages: Does Sectoral Composition Matter for Pakistan?. World Applied Sciences Journal, 21 (6): 915-919.Sugiyono. (2015) Metde Penelitian Pendidikan (pendekatan kuantitatif, kualitatif, dan R&D). Bandung: Alfabeta.Tambunan, T. (2011).  Perekonomian Indonesia, Kajian Teoritis dan Analisis Empiris, Jakarta.: Ghalia Indonesia.Todaro, M. P. (.2000). Pembangunan Ekonomi di Dunia Ketiga Edisi VII, Jakarta: Erlangga,Todaro, P. S. dan Smith, C. S. (2011). Pembangunan Ekonomi Edisi Kesebelas. Jakarta:Erlangga.